Heterodoxa dalam gerakan perlawanan perempuan Indonesia pada film “Kartini” - Bilhaq, Aulia Mardhatillah (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
Patriarchal culture is a culture that is inherent and developing in Indonesia. This culture assumes a position of power in the male group. Kartini as an Indonesian hero is known to be able to produce ideas that are resistance in nature and has succeeded in influencing the culture of domination that exists to this day. Even though Kartini lived at a time when power relations were very strong, especially at a time when Indonesia was still not independent. Kartini's struggle against male domination was immortalized in the film entitled "Kartini". This research aims to see the process of Kartini's success in opposing culture and doxa through Pierre Bourdieu's thoughts regarding Post-Structuralism. In his thoughts, Bourdieu mentions several concepts, namely habitus, capital, arena and doxa which will then be associated with this film. This research uses descriptive qualitative methods with text analysis techniques to explain this process through existing film footage. From this research it can be concluded that Kartini has aspects of habitus, capital and arena that support the success of her thinking which originates from her position in society. So this can provide changes to the surrounding environment. Kartini's habitus, capital and arena are of great value and give her an advantage in establishing dominance in the area she is targeting. Heterodoxa requires high levels of dominance by its actors. The film "Kartini" shows how Kartini's dominance is able to shape a change, especially in the structures that previously existed in society.